Desenvolvimento de métodos eletroquímico e por eletromigração para determinação de zinco, ácido ascórbico, escopolamina e brometo de butilescopolamina em amostras farmacêuticas e de interesse forense - Ribeiro, Michelle Miranda de Araújo Carvalho (2022)
In this thesis two simple and fast methods were developed for simultaneous determination of zinc (Zn) and ascorbic acid (AA) in pharmaceuticals samples and one method for fast and simultaneous determination of scopolamine (SCO) and scopolamine N-butylbromide (BSCO) in pharmaceutical and beverage samples. For Zn and AA determination, one method was based on batch injection analysis with square wave voltammetric detection (BIA-SWV) and other based on capillary electrophoresis with contactless conductivity detection (CE-C4D). Simultaneous determination of SCO and BSCO was also performed by CE-C4D. For the determination of Zn and AA by BIA-SWV, linear ranges from 0.5 to 20.0 μmol L-1 and from 18.5 to 370 μmol L-1 were obtained with limit of detection (LOD) of 0.2 and 5.4 μmol L-1 for Zn and AA, respectively. In the determination of Zn and AA by CE-C4D, linear ranges from 50 to 400 μmol L-1 and from 1850 to 14800 μmol L-1 were obtained with LOD of 10 and 20 μmol L-1 for Zn and AA, respectively. In both methods, samples were prepared by simple dilution in deionized water or supporting electrolyte. The simultaneous determination of SCO and BSCO by CE-C4D was performed in beverage samples without and with dilution in water (10% v/v). Linear ranges between 10 and 1000 μmol L-1 were obtained for both species with LOD of 2.4 and 2.8 μmol L-1 for SCO and BSCO, respectively. Recovery studies were performed with and without flush procedure between injected samples. Recovery values ranged from 100 to 111% for SCO and from 90 to 114% for BSCO were obtained for beverage samples without flush procedure, and from 95 to 112% for SCO and 90 to 105% for BSCO for samples with flush procedure between analysis). Finally, recovery values of 91 to 111% for SCO and 82 to 100% for BSCO were obtained for undiluted beverage samples with flush procedure between analysis. The CE-C4D method also proved to be useful for detecting the formation of SCO (hallucinogenic compound) from heating a buscopan® tablet that contains BSCO in its composition.